EFEK RESIDU PUPUK TRICHO-KOMPOS LIMBAH JAGUNG DAN ROCK PHOSPHATE TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN JAGUNG MANIS (Zea mays Var. saccharata Sturt) DI LAHAN GAMBUT - Pauji Dalimunthe; Armaini Armaini; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this study was to determine the residual effects combination of fertilizers Tricho- compost waste corn with rock phosphate, well as getting the best residual for growth and production of sweet corn on peatlands. This research has been conducted in the Village District of Panam Tuah Karya Tampan, Pekanbaru from January to April 2016. This study is a continuation research conducted experiments using a randomized block design (RAK). The treatmeant has been given to research, so the treatmean in the study is composed of residue combination Tricho-compost waste corn with rock phosphate that is: without giving Tricho-compost waste corn with rock phosphate (T0P0), 0 ton/ha and 50 kg/ha (T0P1), 0 ton/ha and 100 kg/ha (T0P2), 0 ton/ha and 150 kg/ha, 5 ton/ha and 0 kg/ha (T1P0), 5 ton/ha and 50 kg/ha T1P1), 5 ton/ha and 100 kg/ha (T1P2), 5 ton/ha and150 kg/ha (T1P3), 10 ton/ha and 0kg/ha (T2P0), 10 ton/ha dan 50 kg/ha (T2P1), 10 ton/ha dan 100 kg/ha (T2P2), and 10 ton/ha and 150 kg/ha (T2P3). Parameters measured were plant height, diameter rod, the time appears the male flowers, the time appears the female flowers, harvesting, corncob weight, the weight of cob without husk, the length of the cob without husk and the biomass. The results showed that the residual effects combination Tricho- compostable waste corn with rock phosphate significantly affected plant height, diameter rod, time appears the male flowers, female flowers appear time, and the biomass plant. Residual effect of combination 10 tons of Tricho-compost waste corn with 150 kg rock phosphate/ha tend to give the best results on the growth and production of sweet corn on peatlands. Keyword : Sweet corn, Tricho-compost waste corn, Rock phosphate, Peat